Cocrystals, salts and eutectics of anti-tuberculosis medicines - Matlapeng, Tsebang Alice (Rhodes University, Faculty of Science, Department of Chemistry)
Tuberculosis remains as a prominent cause of death worldwide. This infectious disease is treated with first and second line drugs. However, challenges of multi drug resistant tuberculosis and adverse side effects such as depletion of essential B group vitamins in the body by first line drugs, as well as poor physicochemical properties of second line drugs persist. Cocrystallisation of anti-tubercular drugs with various coformers has therefore been used as an alternative method to improve the physicochemical properties of active pharmaceutical ingredients (API) while maintaining their efficacy. The main objective of this study was to carry out cocrystal screening of anti-tubercular API and vitamin B coformers to make drug-drug or drug-vitamin multicomponent complexes. Preparation of the multicomponent complexes was carried out by mechanochemical grinding (neat grinding (NG), liquid assisted grinding (LAG) and slow evaporation. All complexes were characterised using Fourier-transform infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and crystal structures were elucidated using single-crystal X-ray diffraction (SCXRD). The cocrystal screening resulted in the formation of various solid forms, which included cocrystals, salts and eutectic products. Two cocrystals of 4-aminosalicylic acid (PAS) were isolated and characterised. The cocrystal of PAS with isoniazid (INH) demonstrated similar characteristics for both the bulk crystalline material and milled materials. The cocrystal of PAS and pyrazinamide (PYR) prepared using mechanochemical synthesis was met with challenges, while difficulties were also encountered in obtaining suitable crystals for SCXRD analysis. The ground and recrystallised samples of the PAS and pyrazinecarboxylic acid (PCBA) showed distinct differences in their thermal behaviour, with SCXRD revealing the decomposition product phenolammonium-pyrazinecarboxylate salt 'sans' the CO2 moiety. Salt formation involving pyridoxine (PN) yielded a salt hydrate with PAS (PN-PAS) and an anhydrous salt with PCBA (PN-PCBA). Both salts exhibited very complex packing arrangements with equally complex thermal behaviour depending on the solvent used during preparation, and the method of preparation. Three eutectic systems involving INH with PYR, PN and pyridoxine hydrochloride (PNêž HCl) were identified, and their phase diagrams were constructed from DSC data. The eutectic compositions obtained were 1:1 for INH:PYR, 1:1 for INH:PN and 6:4 for INH:PNêž HCl. Finally, a total of eight multicomponent complexes were prepared using selected API and vitamin B6 components. The results presented here provide motivation for further investigation and evaluation of the pharmacochemical properties of these API.
Keywords: Cocrystal; Tuberculosis; 4-aminosalicylic acid; Isoniazid; Pyrazinamide; Pyrazinoic acid